The Effect of Passive Heat Stress and Exercise-Induced Dehydration on the Compensatory Reserve During Simulated Hemorrhage. (September 2016) - Gagnon, Daniel; Schlader, Zachary J.; Adams, Amy; Rivas, Eric; Mulligan, Jane; Grudic, Gregory Z.; Convertino, Victor A.; Howard, Jeffrey T.; Crandall, Craig G.
Abstract : ABSTRACT: Compensatory reserve represents the proportion of physiological responses engaged to compensate for reductions in central blood volume before the onset of decompensation. We hypothesized that compensatory reserve would be reduced by hyperthermia and exercise-induced dehydration, conditions often encountered on the battlefield. Twenty healthy males volunteered for two separate protocols during which they underwent lower-body negative pressure (LBNP) to hemodynamic decompensation (systolic blood pressure <80 mm Hg). During protocol #1, LBNP was performed following a passive increase in core temperature of ∼1.2°C (HT) or a normothermic time-control period (NT). During protocol #2, LBNP was performed following exercise during which: fluid losses were replaced (hydrated), fluid intake was restricted and exercise ended at the same increase in core temperature as hydrated (isothermic dehydrated), or fluid intake was restricted and exercise duration was the same as hydrated (time-match dehydrated). Compensatory reserve was estimated with the compensatory reserve index (CRI), a machine-learning algorithm that extracts features from continuous photoplethysmograph signals. Prior to LBNP, CRI was reduced by passive heating [NT: 0.87 (SD 0.09) vs. HT: 0.42 (SD 0.19) units, P <0.01] and exercise-induced dehydration [hydrated: 0.67 (SD 0.19) vs. isothermic dehydrated: 0.52 (SD 0.21) vs. time-match dehydrated: 0.47 (SD 0.25) units; P <0.01 vs. hydrated]. During subsequent LBNP, CRI decreased further and its rate of change was similar between conditions. CRI values at decompensation did not differ between conditions. These results suggest that passive heating and exercise-induced dehydration limit the body's physiological reserve to compensate for further reductions in central blood volume.